1998
DOI: 10.1111/1469-8986.3520162
|View full text |Cite
|
Sign up to set email alerts
|

Relations between PET‐derived measures of thalamic glucose metabolism and EEG alpha power

Abstract: Electroencephalogram (EEG) alpha power has been demonstrated to be inversely related to mental activity and has subsequently been used as an indirect measure of brain activation. The thalamus has been proposed as an important site for modulation of rhythmic alpha activity. Studies in animals have suggested that cortical alpha rhythms are correlated with alpha rhythms in the thalamus. However, little empirical evidence exists for this relation in humans. In the current study, resting EEG and a fluorodeoxyglucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(65 citation statements)
references
References 28 publications
5
60
0
Order By: Relevance
“…Sensorimotor gating alterations as measured by prepulse inhibition [62] were also shown to correlate with disturbed thinking (Rohrschach test) and delusions (SAPS). Another EEG approach suggested that Norra/Waberski/Kawohl/Kunert/Hock/ Gobbelé/Buchner/Hoff cortical EEG alpha rhythm is correlated with alpha rhythm recorded from the thalamus and related thalamic neuronal activity expressed as glucose metabolic rate in humans [63]. However, this pattern was not observed in schizophrenics [64].…”
Section: Discussionmentioning
confidence: 99%
“…Sensorimotor gating alterations as measured by prepulse inhibition [62] were also shown to correlate with disturbed thinking (Rohrschach test) and delusions (SAPS). Another EEG approach suggested that Norra/Waberski/Kawohl/Kunert/Hock/ Gobbelé/Buchner/Hoff cortical EEG alpha rhythm is correlated with alpha rhythm recorded from the thalamus and related thalamic neuronal activity expressed as glucose metabolic rate in humans [63]. However, this pattern was not observed in schizophrenics [64].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that levels of apoD are particularly elevated in the amygdala and in the thalamus in schizophrenic patients compared to those with bipolar disorder [15]. Although there has been significant debate concerning the meaning and origin of EEG α; ample evidence suggests that these oscillations arise from the thalamic nuclei [47], especially those arising from the nucleus reticularis [48]. Not surprisingly, one of the NE pathways projecting from the LC arrives in thalamus, and it is our hypothesis that elevated levels of apoD could disturb normal thalamic functioning, arising in changes in EEG α oscillations which are related to creative thought processes at baseline and during active problem solving.…”
Section: Apod May Mediate Thalamic States Present During Creative Thomentioning
confidence: 99%
“…Negative symptoms were correlated with decreased thalamic perfusion on SPECT in schizophrenia, as was neuroleptic responsiveness [27], also suggesting a functional relationship [28]. EEG alpha power was correlated with thalamic glucose metabolism in normal subjects [29,30], while this relationship was not found in depressed patients [30]. However, the relationship between GMR in the thalamus as a subcortical structure and alpha rhythm activity measured by quantitative EEG has not yet been studied in patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%